ANDIL KITA DALAM MISI MASA KINI - Purnawan Tenibemas (Sekolah Tinggi Alkitab Tiranus, 2019)
Since Jesus the Lord gave the Great Commission, the current world population that are affiliated to God’s Church is only 33% of the total population. The Great Commission is a must mandate (Luk. 24:47) because of the sinfulness of human and their powerlessness to save themselves from the wrath of God. The sinfulness makes the salvation in Christ to be absolutly needed. The growth of world population is faster than biological growth of Chruch community. Currently, the world population is almost 7.6 billion. Twenty centuries have passed, in terms of its growth, it is an impossibility if Christians just rely on biological growth. This article is aimed to exhibit that the faithfulness of Christians to continue the mission of the Great Mission is an imperative need. The Three Windows has existed and becomes a crucial challenge in the present time. Accordingly, the variety of missionaries and Christians contributions should become serious consideration for all Christians.